Electro-Osmotic Dehydration of Hangzhou Sludge with Selected Electrode Arrangements. Issue 1 (2nd January 2016) - Tao, Yanli; Zhou, Jian; Gong, Xiaonan; Hu, Pingchuan
ABSTRACT: Electro-osmosis is considered a promising technique for the dehydration of sludge with low permeability and high water content. With little information available on the optimal electrode arrangement for electro-osmosis, comparisons of rectangular, hexagonal, and staggered arrays were performed based on laboratory experiments and theoretical analysis. Experimental results identified that favorable electro-osmotic effects were produced by the hexagonal array with regard to drainage, water content, and shear strength of treated soils compared to the other two arrays examined; the average coefficient of energy dissipation of the hexagonal array was 39% lower than that of the rectangular array and 53% lower than that of the staggered array. This finding demonstrates that the hexagonal array consumed less energy. To describe the electro-osmotic efficiency, the effective electric field theory previously proposed was used to calculate proportions of effective field areas; the results show that the hexagonal array performed best, followed by the rectangular and finally the staggered arrays. It is thus concluded that the hexagonal array was most effective and was thus recommended as the primary pattern for application. The validity of the effective electric field theory in estimating electric field distributions for electro-osmosis was also confirmed by comparing theoretical predictions and experimental results.